Linear Algebra - Petersen, Peter (New York : Springer, 2012)
This textbook on linear algebra includes the key topics of the subject that most advanced undergraduates need to learn before entering graduate school. All the usual topics, such as complex vector spaces, complex inner products, the Spectral theorem for normal operators, dual spaces, the minimal polynomial, the Jordan canonical form, and the rational canonical form, are covered, along with a chapter on determinants at the end of the book. In addition, there is material throughout the text on linear differential equations and how it integrates with all of the important concepts in linear algebra.
Basic theory -- Linear operators -- Inner product spaces -- Linear operators on inner product spaces -- Determinants.
Includes bibliographical references (p. 429) and index.
Keywords: Algebras, Linear; Linear Algebra; Mathematics